2013
DOI: 10.1179/1743289813y.0000000051
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium carbonate morphology on thermal and mechanical properties of HDPE

Abstract: Calcium carbonate (CaCO 3 ) microparticles with four different morphologies, which are cubic, acicular, spindle and sphere-like, were prepared using calcium chloride (CaCl 2 ) and sodium carbonate (Na 2 CO 3 ) aqueous solutions containing various additives. High density polyethylene (HDPE)/CaCO 3 composites were prepared using a HAAKE Rotational Rheometer. The thermal behaviour, mechanical properties and the rheology property were investigated and characterised by thermogravimetric analysis (TGA), differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…After adding BPF, nano-CaCO3, and WM in the shell layer, the interfacial compatibility between the core and shell was affected, resulting in a lower impact fracture toughness. These results are supported by other experiments about WPCs (Shi et al 2013). The properties of the core-shell structured BPCs were dependent on the filler's dispersion and adhesion in the polymer matrix.…”
Section: Characterization Of the Samplessupporting
confidence: 86%
“…After adding BPF, nano-CaCO3, and WM in the shell layer, the interfacial compatibility between the core and shell was affected, resulting in a lower impact fracture toughness. These results are supported by other experiments about WPCs (Shi et al 2013). The properties of the core-shell structured BPCs were dependent on the filler's dispersion and adhesion in the polymer matrix.…”
Section: Characterization Of the Samplessupporting
confidence: 86%
“…Therefore, the crystallization of HDPE molecules could occur at a higher temperature. Some similar results have been reported by Shi et al (2013) and Colom et al (2000). However the crystallinity of the composites decreased initially, and then they increased.…”
Section: Thermal Properties Thermogravimetrysupporting
confidence: 80%
“…As the WM content increased, the Tonset of composites increased from 100.58 °C to 107.57 °C. A possible explanation for this was that a small amount of WM acted as a nucleating agent during the crystallization of HDPE, such that the activation energy of HDPE was reduced (Shi et al 2013). The crystallinity of BPCs decreased with lower WM content (14 wt%), indicating the presence of a small amount of WM that adsorbed in the cracks in the BRFs.…”
Section: Thermal Properties Thermogravimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The impact strength of WM-filled BPCs decreased significantly, due to the fact that the micro/nano WM filling effect was poor or hard to fill in tiny gaps of BRF and HDPE, yet they are profoundly incompatible and there were more local stress concentrations generated in the BPCs, so that cracks tend to grow and spread. This can be seen from SEM images of BPCs (Figure 6); it was found that no visual effectively filling was evident in the BPCs [31]. Besides, the compatibility between the WM and HDPE becomes poor with the increasing amount of WM, which led to unstable interfacial adhesions [32].…”
Section: Resultsmentioning
confidence: 99%